2016
DOI: 10.1093/heapro/daw063
|View full text |Cite
|
Sign up to set email alerts
|

Which ecological determinants influence Australian children’s fruit and vegetable consumption?

Abstract: This study investigated determinants of fruit and vegetable (F&V) consumption among regional and remote Western Australian (WA) children, using an Ecological Model of Health Behaviour. Semi-structured interviews were conducted with 20 key informants (Health Workers, Food Supply Workers, and School/Youth Workers) purposively sampled from across regional and remote WA. Interviews were transcribed, analysed thematically using QSR-NVivo 10 software, and embedded within an Ecological Model of Health Behaviour to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Moreover, they also addressed disadvantaged young individuals [37,56,61]. In line with the authors that focused on NL, these researchers which discussed FL considered some social factors that affected FL: socioeconomic level [3,38,56,57,62], education, and literacy [3,23,56,[62][63][64][65].…”
Section: Antecedents Of Flmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, they also addressed disadvantaged young individuals [37,56,61]. In line with the authors that focused on NL, these researchers which discussed FL considered some social factors that affected FL: socioeconomic level [3,38,56,57,62], education, and literacy [3,23,56,[62][63][64][65].…”
Section: Antecedents Of Flmentioning
confidence: 95%
“…On the other hand, Ronto et al focused also on the school organization considering the presence and characteristics of school canteens [24,65], school kitchens [24], and the adherence to the National Healthy School Canteen Guidelines [64]. According to authors' point of view stated in eight papers, individuals closer to the subject (i.e., parents, teachers, and peers) may represent important elements to provide specific knowledge and competences to young people [56,57,[62][63][64][65]67,68]. In addition, the characteristics and factors of the home environment (i.e., family demographics) may influence individuals' FL [62][63][64][65].…”
Section: Antecedents Of Flmentioning
confidence: 99%
See 1 more Smart Citation
“…6,17 Our previous research suggested this was, in part, due to the contribution many remote schools made to children's F&V intake through breakfast or lunch programs. 18 The differences in F&V types and varieties consumed by regional and remote children participating in this study could result from higher availability, affordability and quality produce in some locations. 18 Strengths of this study included using a caregiver-child dyad to provide an understanding of F&V consumption from two perspectives.…”
Section: Discussionmentioning
confidence: 93%
“…18 The differences in F&V types and varieties consumed by regional and remote children participating in this study could result from higher availability, affordability and quality produce in some locations. 18 Strengths of this study included using a caregiver-child dyad to provide an understanding of F&V consumption from two perspectives. Children completed the 24-h food diary, which measured children's consumption of F&V varieties.…”
Section: Discussionmentioning
confidence: 93%